PUBLIC SPHERE’S PRIVATIZATION THROUGH SOCIAL MEDIA ACCOUNT - Ahmad Rudy Fardiyan; Sarwoko Sarwoko (Metakom, 2021)
Internet as a medium that offers an alternative public sphere turns out to raise the issue of bias between public or private’s information. The ambiguity of public and private sphere on the internet is increasingly apparent with the presence of privacy settings features on social media accounts. This research aims to find out the meaning and use of social media accounts as a space for expression of social media account owners. The method used is qualitative by with an interview and observation on a social media accounts and its owners. The results showed that although informants are aware that their social media are public sphere, the content which they uploaded on social media is a private contents. It is considered private because it has no relevance to public affairs. Informants consider their social media accounts as an albums of memorabilia that record the activity of its owners